2017
DOI: 10.1080/09553002.2017.1388547
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation biology of male brown marmorated stink bugs: is there scope for the sterile insect technique?

Abstract: Lack of a dose response at the F generation precludes the use of irradiation-induced inherited sterility. The conventional sterile insect technique appears possible by irradiation of males from ∼12 to 16 Gy. The effect of radiation dose on females is not known, thus we cannot conclude whether bi-sex release is feasible so for now the release of males only is recommended. More work is needed on the competitive fitness of irradiated males, and logistics such as mass rearing or field collection, in order to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
44
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(67 citation statements)
references
References 34 publications
12
44
11
Order By: Relevance
“…As the last development stage of nymphs were used for irradiation experiments here, potentially we are observing that newly emerged adults might be more sensitive to radiation than fully mature nymphs. Welsh et al (2017) reported that the longevity of female insects was negatively affected by its irradiated male partner at doses above 32Gy [20]. We did not observe the effect in our study (p=0.6849, Table 1).…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations
“…As the last development stage of nymphs were used for irradiation experiments here, potentially we are observing that newly emerged adults might be more sensitive to radiation than fully mature nymphs. Welsh et al (2017) reported that the longevity of female insects was negatively affected by its irradiated male partner at doses above 32Gy [20]. We did not observe the effect in our study (p=0.6849, Table 1).…”
Section: Discussioncontrasting
confidence: 73%
“…Normally, the insects should be irradiated at the early stage when the sperm cells are not well developed to get high effectiveness [17]. In the case of BMSB which is an incomplete metamorphic insect species, our results suggest that the SIT can be applied for BMSB management when irradiating nymphal stage insects at doses from 16-64Gy, complementary to previous research conducted by Welsh et al (2017) and Suckling et al (2019) [20,21].…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Host range testing was conducted on several non-target pentatomid bugs [17]. New Zealand has an official government goal of harnessing 4.7 million pairs of eyes for biosecurity [18], and has a long and successful track record of unwanted arthropod eradications [19], as well as a desire to avoid non-target impacts from new parasitoids where possible [20], leading to our search for possible alternative eradication technologies, such as the sterile insect technique [21].…”
Section: Introductionmentioning
confidence: 99%